EFEKTIFITAS PEMBELAJARAN OPEN-ENDED TERHADAP KEMAMPUAN BERPIKIR LOGIS MATEMATIKA SISWA SEKOLAH DASAR - Marzuki Ahmad; Dwi Putria Nasution (DIRASATUL IBTIDAIYAH, 2022)
The low ability of students to think logically in learning is the main problem in this study. Open-ended learning is a learning approach that provides opportunities for students to explore problems so that various and varied solutions are found that can stimulate the development of students' mathematical logical thinking skills. The purpose of this study was to describe the effectiveness of the application of an open-ended learning approach in teaching students' mathematical logical thinking skills. This research is a quasi-experimental research with Non Equivalent Control Group Design. The population of the study was 5th grade students of SDN 100201. Through purposive sampling technique, class 5-B was appointed as the research sample. Data collection was used through observation of learning activities and tests which included pretest and posttest. The data analysis technique used descriptive analysis, t-test and N-gain. The data from the observation of learning management conducted in two meetings gave an average score of 4.05 (good category). The data obtained from the significance of the logical thinking ability of students' t-test score is 0.000, which means that there is a significant difference in the similarities of the two average students' logical thinking abilities from the results of the pretest and posttest. The average value of the N-Gain of students' mathematical logical thinking skills is 0.38 (medium category). It was concluded that students' mathematical logical thinking skills through open-ended learning were effective in the medium category.Keywords: Learning, Open-ended, Logical Thinking, Mathematics, Elementary School.